2019
DOI: 10.36778/jesya.v2i1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compensation on Employee Performance at PT. Sango Indonesia - Karawang

Abstract: Employee performance is very important for the achievement of the goals of a company. One important factor that can affect performance in a company is from providing compensation given to employees. Compensation is something that is received by employees as a substitute for their service contribution to the company. The existence of a good compensation system will ensure the occurrence of justice between employees and the company. Each employee will receive a reward in accordance with the goals, functions, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The provision of compensation which is one of the important factors in influencing employee performance is the existence of fair and equitable compensation. Several previous research results empirically confirm that compensation has a positive and significant effect on performance (Hameed et al, 2014;Dwianto et al, 2019). The results showed that the work environment and compensation had a significant positive effect on employee performance simultaneously.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The provision of compensation which is one of the important factors in influencing employee performance is the existence of fair and equitable compensation. Several previous research results empirically confirm that compensation has a positive and significant effect on performance (Hameed et al, 2014;Dwianto et al, 2019). The results showed that the work environment and compensation had a significant positive effect on employee performance simultaneously.…”
Section: Discussionsupporting
confidence: 56%
“…work, their personal contribution, and performance (Dwianto et al, 2019;Sudiardhita et al, 2018;Suharyat & Danapriatna, 2021;Wekesa & Nyaroo, 2013). This assumption means that compensation is one of the physical needs that affect a person's motivation which in turn affects their performance.…”
Section: {3mentioning
confidence: 99%
See 1 more Smart Citation
“…In carrying out the production process, a company needs production factors that can support the achievement of company goals, such as raw materials, capital, and people. Especially in the human factor, this factor plays a very important role in carrying out the production process (Dwianto, Purnamasari, & Tukini, 2019). Human Resources (HR) play a very important role in the company because it is humans who manage other resources in the company/organization so that they become useful.…”
Section: Introductionmentioning
confidence: 99%
“…Compensation does not affect work motivation. Dwianto et al, (2019), researched on the Effect of Compensation on Employee Performance at PT. Sango Indonesia.…”
Section: Introductionmentioning
confidence: 99%